The molecular biology of senile plaques and neurofibrillary tangles in Alzheimer’s disease - Armstrong, Richard A. (Folia Neuropathologica, 2009)
Since the earliest descriptions of the disease, senile plaques (SP) and neurofibrillary tangles (NFT) have been regarded as the pathological ‘hallmarks’ of Alzheimer’s disease (AD). Whether or not SP and NFT are sufficient cause to explain the neurodegeneration of AD is controversial. The major molecular constituents of these lesions, viz., ß-amyloid (Aß) and tau, have played a defining role both in the diagnosis of the disease and in studies of pathogenesis. The molecular biology of SP and NFT, however, is complex with many chemical constituents. An individual constituent could be the residue of a pathogenic gene mutation, result from cellular degeneration, or reflect the acquisition of new proteins by diffusion and molecular binding. This review proposes that the molecular composition of SP and NFT is largely a consequence of cell degeneration and the later acquisition of proteins. Such a conclusion has implications both for the diagnosis of AD and in studies of disease pathogenesis.